Promoting Islam Nusantara: A Lesson from Nahdlatul Ulama (NU) - Murtaufiq , Sudarto (LPPPM STAI Darul Hikmah Bangkalan, 2018)
NU has explicitly voiced the importance of the Muslims within and outside the country to reconsider and rethink the concept of Islam Nusantara. It is such a historical consciousness could be seen clearly from the roles played by the religious social organization in materializing the teachings of Ahlussunnah wal jamaah (Aswaja). In this capacity, NU has been capable of brilliantly articulated religious teachings that are at least based on three aspects, namely the normative doctrinal, historical and cultural. The success of NU in propagating the the concept of Islam Nusantara is due to the role of its prominent clerics and Muslim scholars (ulema) for skilfully being able to sow the seeds of Islamic teachings in a peaceful and courteous means in the face of different cultures, traditions and customs inherited and developed by the so-called Walisongo. On this stand, NU is committed to doing its best services for the country and even taking part in internationalizing its moderate and tolerant teachings of Islam to other countries